Multivariable Classification of Countries of the World in Terms of Innovation Development - Victorovna Kuznetsova, Natalia; Victorovna Kocheva, Ekaterina; Anatolievich Matev, Nikolay (International Journal of Engineering and Technology, 2018)
The article makes an attempt to contribute to the scientific literature on the issues of directions of intercountry integration from the point of innovative development and understanding of a new structure of integration associations of countries, leaders of innovation development, which will determine the top level of development. The results of the multivariable classification of 189 countries in terms of innovative development show that the countries are divided into five clusters. Moreover, the leading countries that form the "core" of the cluster are identified within each group. Also, there is a high differentiation in all indicators characterizing innovation development of the countries as evidenced by the calculated coefficients of variation.Â Â